2015
DOI: 10.1111/odi.12349
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic properties of ultrasound of major salivary glands in Sjögren's syndrome: a meta‐analysis

Abstract: The quality of current studies is low, thus not allowing to judge the likelihood of salivary gland ultrasonography as a reliable and practical tool in diagnosing Sjögren's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 39 publications
2
55
0
2
Order By: Relevance
“…Our findings regarding the sensitivity and specificity of sUS outcome compared with the classification criteria for pSS are similar with the results described in a recent meta-analysis 8. Sensitivity of sUS was lowest when compared with the recently published ACR-EULAR criteria, when either parotid or labial gland biopsies were considered as an item for classification.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings regarding the sensitivity and specificity of sUS outcome compared with the classification criteria for pSS are similar with the results described in a recent meta-analysis 8. Sensitivity of sUS was lowest when compared with the recently published ACR-EULAR criteria, when either parotid or labial gland biopsies were considered as an item for classification.…”
Section: Discussionsupporting
confidence: 89%
“…A recent meta-analysis assessing the diagnostic properties of sUS in pSS reported a pooled sensitivity of 69% and specificity of 92%. This meta-analysis also revealed a large clinical and methodological heterogeneity between studies, which hampered interpretation of pooled outcomes and influenced the results reported in the various studies 8. Thus, the possible role of sUS in the diagnosis of pSS remains unclear 8–10…”
Section: Introductionmentioning
confidence: 99%
“…Like Cornec et al , we also feel that ultrasound has merit in the diagnosis and assessment of the disease activity of pSS 1 14 15. However, before making salivary gland ultrasound a standard in pSS diagnostics, disease monitoring and treatment evaluation, there are several questions that need to be answered first, that is, the reliability of ultrasound in the evaluation of changes that occur in the major salivary glands of patients with pSS, and the validity of ultrasound to detect the histopathological changes occurring in the parotid tissue of patients (suspected) with pSS (in particular direct comparison of ultrasonographical and histopathological features).…”
Section: Salivary Gland Ultrasoundsupporting
confidence: 56%
“…Based on a recent meta-analysis,3 the Hocevar scoring system7 was incorporated in our daily clinical practice to address all relevant aspects of sUS, since this system appeared to most comprehensive and was therefore also recently applied in our reliability and validity studies 6 10. As mentioned before, more simple scoring systems have been used previously,11–14 but, to the best of our knowledge, none of these simpler scoring systems were constructed applying a multivariate regression model.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has recently identified 33 scoring systems used to evaluate the major salivary glands in patients with SS 3. This heterogeneity within the scoring systems was related to the type of salivary glands examined, the ultrasonographic characteristics evaluated and the cut-off points applied.…”
Section: Introductionmentioning
confidence: 99%